An intergrated strategic management model to navigate the establishment of transport authorities - Chris A. Geldenhuys; Louis Naudé; Theo H. Veldsman (SA Journal of Human Resource Management, 2003)
This research covered the strategic intent for the transport industry and an overview of Transport Authorities in the municipal sphere of government. Representative sets of strategic management and change navigation models, as well as Swanepoel’s (2001) model being used in the management of change in the public sector, were reviewed. An integrated strategic management model, which incorporates principles from strategic management and change navigation, is proposed for navigating the establishment of Transport Authorities. This model consists of six phases, namely: Awareness and Mobilisation; Strategic Synthesis and Choice; Strategy Crafting; Strategy Implementation; Performance Monitoring and Review; and Stabilisation. Recommendations follow regarding the validation of the model in a pilot project.